2017
DOI: 10.4049/jimmunol.1601745
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Nlrp3 Augments Survival during Polymicrobial Sepsis by Decreasing Autophagy and Enhancing Phagocytosis

Abstract: NLRP3 inflammasome is a critical player in innate immunity. Neutrophil recruitment to tissues and effective function of neutrophils are critical innate immune function to bacterial clearance. However, the role of NLRP3 in neutrophil-dependent bacterial clearance in polymicrobial sepsis is unclear. Herein, we evaluated the role of NLRP3 in polymicrobial sepsis induced by cecal ligation and puncture (CLP). Our results exhibit protection from death in NLRP3-deficient (Nlrp3−/−) and NLRP3 inhibitor-treated wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 66 publications
2
64
0
Order By: Relevance
“…The underlying mechanism suggested to confer this protective effect in NLRP3-deficient mice was decreased autophagy and increased phagocytosis by neutrophils. 49 The role of NLRP3 in Salmonella typhimurium infection remains elusive, 50 with one study suggesting of a muti-protein complex formed in macrophages in the presence of S. typhimurium infection, which is composed of NLRP3 and NLRC4, both being required for IL-1b processing. 51 Helicobacter pylori features two contradicting traits-whereas cagA-positive strains were shown to activate the inflammasome to exacerbate DSS-induced colitis and to promote carcinogenesis, 52 other studies demonstrated that H. pylori infection conferred protection from DSS-induced colitis, both clinically and histopathologically, by the induction of the Muc2 gene and production of mucus.…”
Section: Canonical Inflammasomes In Gastrointestinal Physiology Nlrp3mentioning
confidence: 99%
“…The underlying mechanism suggested to confer this protective effect in NLRP3-deficient mice was decreased autophagy and increased phagocytosis by neutrophils. 49 The role of NLRP3 in Salmonella typhimurium infection remains elusive, 50 with one study suggesting of a muti-protein complex formed in macrophages in the presence of S. typhimurium infection, which is composed of NLRP3 and NLRC4, both being required for IL-1b processing. 51 Helicobacter pylori features two contradicting traits-whereas cagA-positive strains were shown to activate the inflammasome to exacerbate DSS-induced colitis and to promote carcinogenesis, 52 other studies demonstrated that H. pylori infection conferred protection from DSS-induced colitis, both clinically and histopathologically, by the induction of the Muc2 gene and production of mucus.…”
Section: Canonical Inflammasomes In Gastrointestinal Physiology Nlrp3mentioning
confidence: 99%
“…Phagocytosis is related to autophagy, a conserved intracellular process that contributes to the degradation and recycling of cellular proteins and organelles to maintain cellular homeostasis. 5 Both phagocytosis and autophagy are involved in host defence and have critical roles in pathogen capture and degradation, respectively. 6 Recent investigations indicated that autophagy plays an essential role in regulating phagocytosis in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 activation induces nuclear factor (NF)-κB mediated proinflammatory cytokine expression (12). Additionally, inflammatory responses are amplified with the induction of NLPR3 in the heart during SIcM (13)(14)(15). The NLRP3 inflammasome, as a member of the NOd-like receptor (NLR) family, is comprised of apoptosis-associated speck-like protein (ASc), caspase-1 and NLRP3.…”
Section: Introductionmentioning
confidence: 99%